2010
DOI: 10.1590/s1807-59322010001000003
|View full text |Cite
|
Sign up to set email alerts
|

The influence of various anesthesia techniques on postoperative recovery and discharge criteria among geriatric patients

Abstract: OBJECTIVE:We aim to compare selective spinal anesthesia and general anesthesia with regard to postoperative recovery and fast‐track eligibility in day surgeries.MATERIALS AND METHOD:Sixty geriatric outpatient cases, with ASA II‐III physical status and requiring short‐duration transurethral intervention, were enrolled in the study. The cases were split into 2 groups: as general anesthesia (Group GA) and selective spinal anesthesia (Group SSA). Group GA (n = 30) received propofol 2 mg kg‐1 (until loss of eyelash… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…We excluded any patients with medical or cardiac diseases to ensure safety even SSA was safe in the current study as regards hemodynamic stability and safe home discharging and that was confirmed in the previous study which studied the effect of SSA on postoperative recovery and discharge criteria among geriatric patients over than 65 years. [ 20 ] in the current study we selected short procedures to be applicable with the concept of ambulatory surgery and we select type of patient as we excluded any cardiac or medical diseases patients, we select age of patients, and type of SSA to ensure rapid, safe, and efficient fast track anesthesia. In our study, we tried to ensure safety to our patients by; written instructions to the patients or their relatives upon home discharging to cover all delayed side effects of spinal as PDPH and TNS.…”
Section: Discussionmentioning
confidence: 99%
“…We excluded any patients with medical or cardiac diseases to ensure safety even SSA was safe in the current study as regards hemodynamic stability and safe home discharging and that was confirmed in the previous study which studied the effect of SSA on postoperative recovery and discharge criteria among geriatric patients over than 65 years. [ 20 ] in the current study we selected short procedures to be applicable with the concept of ambulatory surgery and we select type of patient as we excluded any cardiac or medical diseases patients, we select age of patients, and type of SSA to ensure rapid, safe, and efficient fast track anesthesia. In our study, we tried to ensure safety to our patients by; written instructions to the patients or their relatives upon home discharging to cover all delayed side effects of spinal as PDPH and TNS.…”
Section: Discussionmentioning
confidence: 99%
“…The mode of anesthesia also did not have any significant effects on perioperative outcomes (MI, pulmonary complication, stroke, urinary tract infection, and wound infection) after lower extremity amputation in a total of 3,260 geriatric patients [76]. While anesthesia preparation time, start time of surgery, length of surgery, time to sit, and time to walk were shorter in GA, time to fast-track eligibility, phase 1 recovery time, and time to discharge were similar among patients who received SA [77]. Another 2014 retrospective cohort study that included 56,729 patients ≥ 50 years old undergoing hip repair surgery found that RA was not associated with a lower 30-day mortality when compared with GA (RA, 5.4%; GA, 5.8%; instrumental variable estimate of risk difference, -1.1%, 95% CI -2.8 to 0.5), P = 0.20) but was associated with a modestly shorter length of stay.…”
Section: Mode Of Anesthesiamentioning
confidence: 95%
“…In recent years, it has been shown that perioperative anesthesia management may affect the occurrence of postoperative complications-in particular, infectious complications. 10 For instance, patients who received intravenous propofol anesthesia had a lower incidence of serious postoperative complications and faster asymptomatic recovery after esophageal surgery, compared with patients who received inhalational sevoflurane. 11 Another study found that, among 3081 patients who underwent total hip or knee replacement, general anesthesia was associated with a higher risk of surgical site infection, compared with general anesthesia combined with epidural or spinal anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…13 Studies attempting to identify predictors of infection after gastrointestinal surgery have mainly focused on colorectal surgery, and scant research has been performed on gastric surgery-even more rarely on the association between anesthesia management and postoperative infectious complications after resection for gastric cancer. 14,15 As for the important role of anesthesia on patients' postoperative recovery, [10][11][12][13] this retrospective cohort study was designed to explore the relationship between perioperative anesthesia management and postoperative in-hospital infectious complications in patients who underwent resection for gastric cancer.…”
Section: Introductionmentioning
confidence: 99%